PENGARUH EXPERIENTIAL MARKETING, CUSTOMER DELIGHT, DAN KEPERCAYAAN PELANGGAN TERHADAP NIAT PERILAKU PELANGGAN MELALUI KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING (Studi Kasus Pada Bengkel Resmi Yamaha PT. Roda Sakti Surya Megah) - Anggun Puspita; Chandra Kartika (Universitas 17 Agustus 1945 Surabaya, 2019)
The purpose of this study is to test experiential marketing, customer delight, and customer trust in customer behavior intentions through customer satisfaction. The subjects of this research are Yamaha customers of PT. Roda Sakti Surya Megah as many as 100 people. Sampling in this study using accidental sampling. Data analysis technique used in this study is path analysis. Based on the analysis results, the coefficient of determination show by Adjusted R Square= 0.453 ;. This value indicates that there are any relations between experiential marketing, customer delight and customer confidence in customer satisfaction. Furthermore, based on the research results obtained also obtained the coefficient of determination between the variables experiential marketing, customer delight, and customer trust in customer behavior intentions through customer satisfaction as big as Adjusted R Square = 0.462. This value shows that there is a significant influence between experiential marketing, customer delight, marketers' trust in customer behavior intentions through customer satisfaction. Keywords: experiential marketing, customer delight, customer trust, and customer behavioral intentions.